1986
DOI: 10.3109/03009748609092674
|View full text |Cite
|
Sign up to set email alerts
|

SA 96 (N-(2-Mercapto-2-Methylpropanoyl)-L-Cysteine) in Rheumatoid Arthritis

Abstract: SA 96 (N-(2-mercapto-2-methylpropanoyl)-L-cysteine) is a new sulfhydryl compound having a relatively similar chemical structure to Tiopronin and D-penicillamine. An open trial of SA 96 treatment (300 mg/day after meals for 16 weeks) was carried out in 11 patients with definite or classical rheumatoid arthritis and with therapeutic failure of previous gold salts and/or D-penicillamine therapy. Two cases were withdrawn from the trial, because of a side effect (hepatitis) in one patient and an unrelated illness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Bucillamine (N-[2-mercapto-methylpropanyl]-Lcysteine), was recently developed in Japan as a therapeutic agent for the treatment of rheumatoid arthritis (RA) [5,19]. It is basically a cysteine derivative with two sulfhydryl groups, and its structure bears a striking resemblance to that of D-penicillamine (Fig.…”
mentioning
confidence: 99%
“…Bucillamine (N-[2-mercapto-methylpropanyl]-Lcysteine), was recently developed in Japan as a therapeutic agent for the treatment of rheumatoid arthritis (RA) [5,19]. It is basically a cysteine derivative with two sulfhydryl groups, and its structure bears a striking resemblance to that of D-penicillamine (Fig.…”
mentioning
confidence: 99%
“…In several clinical studies, both bucillamine and D-pen were shown to give the same types of beneficial therapeutic effects in RA patients. Though both compounds seem to affect the disorders of the immune system in RA patients, some differences in response of RA patients have been observed between bucillamine and o-pen, that is, bucillamine showed beneficial effects in some patients who did not respond to o-pen [8]. Such differences in therapeutic responses between bucillamine and D-pen may be correlated with the differences of action of bucillamine and D-pen on lymphocytes as described in this paper.…”
Section: Discussionmentioning
confidence: 74%
“…For example, ])-pen binds to vitamin B 6 and long term administration of D-pen causes vitamin B 6 deficiency, whereas bucillamine does not have any affinity for vitamin B 6 and intake of bucillamine does not result in vitamin B 6 deficiency [7]. It has also been demonstrated that buciltamine shows beneficial effects in some RA patients who do not respond to D-pen [8]. Therefore, in some aspects, bucillamine seems to have some properties which are not observed with D-pen.…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients who develop persistent proteinuria, membranous nephropathy is reported to be seen in 70% or 88% during treatment with gold 4 or D-penicillamine, 5 respectively. Bucillamine (BCL; N-[2-mercapto-2-methypropinil]-lcysteine), a DMARD widely prescribed in Japan, has a chemical structure similar that of to D-penicillamine, 7,8 and is also reported to be a cause of membranous nephropathy. [9][10][11] However, current knowledge of the nephropathy associated with the use of BCL is limited, and, to our knowledge, the clinical course of the nephropathy has not been described in detail.…”
Section: Introductionmentioning
confidence: 99%